(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
In Ayurveda most of the skin diseases are explained under the term Kushtha. Shwitra is considered as one of the varieties of Kushtha in the Ayurvedic Classics, caused vitiation of Tridoshas and Dhatus like Rakta, Mamsa and Meda. The references of Shwitra are found in almost all the Samhitas like Bruhatrayees and Laghutrayees. Partial or complete loss of skin pigmentation giving rise to white patch on any part of the body is called as leucoderma or vitiligo and in Ayurveda it is called as Shwitra. This depigmentation results due to destruction of melanocytes, which may be unknown in origin or due to autoimmune endocrinopathies selective IgA deficiency. A female patient, aged 20 year suffering from white patches in neck region since 4 year was treated with both Shaman Chikitsa and Sodhan Chikitsa for a period to 4 months with follow up at every 30 days in between, Relief from the complaints was assessed by noting the changes in the size of patch. After 4 months of treatment the size of patch was reduced. The present case study revealed the efficacy of Ayurveda therapy both internal and external for duration of 4 months in the management of Shwitra.